Targeting the gut to improve seizure control in CDKL5 deficiency disorder (CDD): study protocol for a single-arm, open-label clinical trial - Triva, Francesca; Borghi, Elisa; Marsiglia, Matteo Domenico; Ottaviano, Emerenziana; Ricci, Emilia; Tognini, Paola; Montecucco, Marco; Vignoli, Aglaia (Frontiers in Neurology, 2025)
IntroductionCyclin-dependent kinase-like 5 deficiency disorder (CDD) is a neurodevelopmental condition characterized by infantile-onset epilepsy, developmental delay, intellectual and motor disabilities, sleep disturbances, and cortical visual impairment. Currently, there is no treatment for CDD, and epilepsy is a prominent and severe feature of the disorder. Standard anti-seizure medications have limited efficacy in seizure control, leading to detrimental effects on cognitive and motor development in CDD. The gut-brain axis has gained attention in epilepsy research, prompted by evidence of gastrointestinal (GI) symptoms in people with epilepsy. Notably, CDD patients experience GI problems and exhibit alterations in their gut microbiota compared to healthy individuals. We propose targeting the gut-microbiota-brain axis in CDD patients to alleviate seizures and potentially ameliorate other symptoms.Methods and analysisThe protocol involves a two-step treatment strategy: a 12-week supplementation with alpha-lactalbumin (ALAC), fructooligosaccharides (FOS), and inulin to reduce inflammation, followed by a 12-week supplementation with ALAC/FOS/Inulin plus Sodium butyrate (NaB), to restore the balance of the gut microbiota. Clinical parameters, including seizure frequency, sleep disturbances, and GI discomfort, will be evaluated. Stool samples will be collected to analyse the gut microbiome. Primary objectives are to determine whether supplementation with ALAC/FOS/inulin alone or in combination with NaB can improve neurological features in CDD and to explore their effects on gut microbiota composition. Our study aims to provide insights into the potential benefits of targeting the gut-brain axis in CDD and offer new therapeutic options to improve seizure control and associated comorbidities.Ethics and disseminationThe study protocol was approved by the local ethics committee (CET 3, n° 4189_17.04.2024_N_bis). Study results will be disseminated by the investigators through presentations at international scientific conferences and reported in peer-reviewed scientific journals.Clinical trial registrationClinicalTrials.gov, Identifier NCT06448663